Refining Risk for Alzheimer's Disease Among Heterozygous APOEɛ4 Carriers - Patel, Smita; Wei, Jun; Shi, Zhuqing; Rifkin, Andrew S; Zheng, S Lilly; Gelfman, Elizabeth; Duggan, David; Helfand, Brian T; Hulick, Peter J; Xu, Jianfeng (Journal of Alzheimer's disease, 2023)
In a large population-based cohort, we show not all heterozygous APOEɛ4 carriers are at increased risk for Alzheimer's disease (AD); a significantly higher AD proportion was only found for ɛ3/ɛ4, not ɛ2/ɛ4. Among ɛ3/ɛ4 carriers (24% in the cohort), the AD proportion differed considerably by polygenic risk score (PRS). In particular, the AD proportion was lower than the entire cohort for subjects in the bottom 20-percentile PRS and was higher than that of homozygous ɛ4 carriers for subjects at the top 5th-percentile PRS. Family history was no longer a significant predictor of AD risk after adjusting APOE and PRS.